The first day of the Cenozoic - Gulick, S.P.S.; Bralower, T.J.; Ormö, J.; Hall, B.; Grice, Kliti; Schaefer, Bettina; Lyons, S.; Freeman, K.H.; Morgan, J.V.; Artemieva, N.; Kaskes, P.; De Graaff, S.J.; et al. (NATL ACAD SCIENCES, 2019)
Highly expanded Cretaceous-Paleogene (K-Pg) boundary section from the Chicxulub peak ring, recovered by International Ocean Discovery Program (IODP)-International Continental Scientific Drilling Program (ICDP) Expedition 364, provides an unprecedented window into the immediate aftermath of the impact. Site M0077 includes ∼130 m of impact melt rock and suevite deposited the first day of the Cenozoic covered by <1 m of micrite-rich carbonate deposited over subsequent weeks to years. We present an interpreted series of events based on analyses of these drill cores. Within minutes of the impact, centrally uplifted basement rock collapsed outward to forma peak ring capped in melt rock. Within tens of minutes, the peak ring was covered in ∼40 m of brecciated impact melt rock and coarsegrained suevite, including clasts possibly generated by melt-water interactions during ocean resurge. Within an hour, resurge crested the peak ring, depositing a 10-m-thick layer of suevite with increased particle roundness and sorting.Within hours, the full resurge deposit formed through settling and seiches, resulting in an 80-m-thick fining-upward, sorted suevite in the flooded crater. Within a day, the reflected rim-wave tsunami reached the crater, depositing a cross-bedded sand-to-fine gravel layer enriched in polycyclic aromatic hydrocarbons overlain by charcoal fragments. Generation of a deep crater open to the ocean allowed rapid flooding and sediment accumulation rates among the highest known in the geologic record. The high-resolution section provides insight into the impact environmental effects, including charcoal as evidence for impactinduced wildfires and a paucity of sulfur-rich evaporites from the target supporting rapid global cooling and darkness as extinction mechanisms.